COMMUNITY ACCESS TO HEALTH SERVICES DURING THE COVID-19 PANDEMIC - Dian Rezki Wijaya; Emmi Bujawati; Sukma Wardani; Andi Islamiyah; Rida Wahida (Homes Journal = Hospital Management Studies Journal, 2023)
During the current Covid-19 pandemic, public visits to health facilities such as hospitals, health centers and clinics have decreased. People are increasingly worried about visiting health facilities for fear of contracting it. The purpose of this study was to measure the level of public concern about visiting a health facility during a pandemic when experiencing health problems. This research is a quantitative research using an analytical approach and study designcross sectional. The population in this study were all Indonesian people and the number of samples in this study were 118 people. The analytical method used is univariate about the respondent's identity (gender, age, occupation, and education) and bivariate to determine the correlation of the independent variables with the dependent variable using the test chi square. The sampling technique uses the technique accidental sampling. The results of the study showed that there was no relationship between the level of knowledge and the level of public concern about visiting health facilities p-value 0.421.